Pengaruh Dukungan Orang Tua dan Motivasi Belajar terhadap Minat Siswa Melanjutkan Pendidikan ke Perguruan Tinggi - Indra Jannatul Addnin; Z. Mawardi Effendi (Universitas Negeri Padang, 2021)
The purpose of this study was to see the effect of parental support and student motivation to continue their education to higher education at SMA Muhammadiyah 2 Padang. This type of research is descriptive quantitative. The population in this study were students of SMA Muhammadiyah 2 Padang. The number of research samples was 60 people and selected using saturated samples. The data used is the type of primary data obtained through distributing questionnaires to predefined students of SMA Muhammadiyah 2 Padang. The analytical method used is multiple regression analysis using SPSS 16. The results show that (1) parental support and learning motivation have a joint influence on students' interest in continuing education to higher education, (2) parental support has an influence on students' interest in continuing education to higher education, (3) learning motivation has an influence on students' interest in continuing education to higher education. interest of students to continue education to college. Keywords : : parental support, learning motivation, student interest